Do Milagre à Abertura: aspectos do regime militar revisitados através de uma análise do filme Pra frente Brasil - Ferreira, Neliane Maria (2006)
This study is considering to board of representation of facts occurred during the Brazilian military dictatorship, more specifically in the year of 1970, showed in the movie Pra Frente Brasil. We search in fixing them in this narrative that promoted to reread of the context politician and social Brazilian of the beginning of year 1970 and through this fílm source we try to catch and to analyze as this and other representations had operated a rescue of that historical moment at the moment of proper characteristics where they had been constructed. In such analysis to became necessary to establish a dialogue between History, Cinema and Fiction and therefore we search theoretical references in the field of the Cultural History, that considers the opening of the fan of documentary sources - as the use of artistic production - for the work of the historian. Pra Frente Brasil is a remade construction of the History that caused great controversy to the launched being, in 1982, year where the country still was governed for military. To the being forbidden for the state censorship, it got great prominence in the journalistic media and was the responsible one for the beggining of a great debate between sectors of the society regarding subjects as censorship, torture, cinema and society. Pra Frente Brasil, when represented a historical context (1970) in other (1982) particularly important to understand questions related to the military dictatorship, to became a reference mainly to think the relation between History and Fiction and between History and Cinema, question on which in we lean over them during the research that resulted in this work.